(untitled) (Research, Society and Development, 2021)
The aim of this study was to analyze the trend of breast cancer mortality rates in women in the state of Santa Catarina, Brazil, between 2000 and 2017. This is an ecological study carried out with death data from the Information System on Mortality and population data obtained from estimates made available by the Ministry of Health. Simple linear and polynomial regression models were used in the analysis. Between 2000 and 2017, 7,363 deaths from breast cancer were recorded in women aged 20 years or over. For the period, 47.5% of the total deaths occurred in the age group from 50 to 69 years (n=3,497). The average breast cancer mortality rate was 18.24/100,000 women (2000-2017). The average mortality coefficients exceeded 30 deaths/100,000 women aged 50 to 59 years, reaching 87.25/100,000 in the longest-lived. In the analysis of the trend, broken down by age groups, it was observed, in general, a non-constant linear increase in the period. The study revealed an increasing trend of mortality from breast cancer in women living in the state of Santa Catarina during the period and showed the magnitude of the increase in the mean coefficients according to the age groups considered.